Untangling nomenclatural issues of some Amazonian trees of Eperua Aubl. (Leguminosae, Detarioideae, Detariae) - Fortes, Elenice A.; Mansano, Vidal F. (Phytotaxa, 2022)
Here we present a further nomenclatural revision of the genus Eperua. We correct the author of one nomenclatural combination, update the status of seven names as illegitimate, and make three lectotypifications and one second-step lectotypification. These nomenclatural changes are made in response to the International Code of Nomenclature for algae, fungi, and plants that aims at stability of biological nomenclature. The present results show that even revised names may still need to be checked and updated.